Festival Anak Sholeh sebagai Sarana Penanaman Nilai Religius dan Rasa Percaya Diri Anak Anak di Desa Jelutih Kecamatan Batin XXIV - Amiruddin Amiruddin; Wahyu Widiyansih; Evi Triutami; Yunis Maila; Wahyu Hidayat; M. Roihan Rangkuti; Piki Para Muja; Alfajri Rahmadani; Maryam Maryam (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The Pious Children Festival is a collaborative work program implemented by students (KKN) of Batang Hari Islamic University in Jelutih Village, Batin XXIV District. This activity aims to instill religious values ​​and strengthen children's self-confidence from an early age. A pious child is defined as an individual who consistently behaves well, possesses strong faith, and is devout in practicing Islamic teachings. The objectives of the Pious Children Festival include: (1) increasing children's enthusiasm for studying Islamic teachings, (2) developing children's interests and talents in religious matters, and (3) fostering children's self-confidence in showcasing their abilities. This activity is packaged in the form of religious competitions that include the call to prayer (adhan), memorization of short surahs (chapters), daily prayers, Qur'an recitation, and an Islamic fashion show. Participants from the PAUD (Early Childhood Education), Kindergarten (TK), and RA (Islamic Elementary School) levels take part. The implementation method involves several stages: analyzing the needs of early childhood children, planning activities, implementing programs, and evaluating and following up on the results. The results of the Pious Children Festival demonstrated an increased enthusiasm among the children of Jelutih Village for learning about Islam. Furthermore, this activity also had a positive impact on increasing the children's courage and confidence in showcasing their religious talents. This was evident in the changes in the attitudes of several boys who previously lacked confidence in performing the call to prayer, but after participating in this activity, became more courageous and confident.